Ωcγ → Ωc* transition in lattice QCD - Bahtiyar, H.; Can, K. U.; Erkol, G.; Oka, M. (ELSEVIER SCIENCE BV, 2015)
We study the electromagnetic Omega(c)gamma -> Omega(c)* transition in 2 + 1 flavor lattice QCD, which gives access to the dominant decay mode of Omega(c)* baryon. The magnetic dipole and the electric quadrupole transition form factors are computed. The magnetic dipole form factor is found to be mainly determined by the strange quark and the electric quadrupole form factor to be negligibly small, in consistency with the quark model. We also evaluate the helicity amplitudes and the decay rate. (C) 2015 The Authors. Published by Elsevier B.V.
Keywords: Charmed baryons; Electric and magnetic form factor; Lattice QCD; RADIATIVE DECAYS; PHOTOPRODUCTION; STRENGTH; Astronomy & Astrophysics; Physics